Feasibility of antiretroviral therapy initiation under the treat‐all policy under routine conditions: a prospective cohort study from Eswatini. Issue 10 (24th October 2019) - Kerschberger, Bernhard; Jobanputra, Kiran; Schomaker, Michael; Kabore, Serge M; Teck, Roger; Mabhena, Edwin; Lukhele, Nomthandazo; Rusch, Barbara; Boulle, Andrew; Ciglenecki, Iza
Abstract: Introduction: The World Health Organization recommends the Treat‐All policy of immediate antiretroviral therapy (ART) initiation, but questions persist about its feasibility in resource‐poor settings. We assessed the feasibility of Treat‐All compared with standard of care (SOC) under routine conditions. Methods: This prospective cohort study from southern Eswatini followed adults from HIV care enrolment to ART initiation. Between October 2014 and March 2016, Treat‐All was offered in one health zone and SOC according to the CD4 350 and 500 cells/mm 3 treatment eligibility thresholds in the neighbouring health zone, each of which comprised one secondary and eight primary care facilities. We used Kaplan–Meier estimates, multivariate flexible parametric survival models and standardized survival curves to compare ART initiation between the two interventions. Results: Of the 1726 (57.3%) patients enrolled under Treat‐All and 1287 (42.7%) under SOC, cumulative three‐month ART initiation was higher under Treat‐All (91%) than SOC (74%; p  <   0.001) with a median time to ART of 1 (IQR 0 to 14) and 10 (IQR 2 to 117) days respectively. Under Treat‐All, ART initiation was higher in pregnant women (vs. non‐pregnant women: adjusted hazard ratio (aHR) 1.96, 95% confidence interval (CI) 1.70 to 2.26), those with secondary education (vs. no formal education: aHR 1.48, 95% CI 1.12 to 1.95), and patients with an HIV‐positive diagnosis before care enrolment (aHR 1.22, 95% CI 1.10 to 1.36). ART initiation was lower in patients attending secondary care facilities (aHR 0.64, 95% CI 0.58 to 0.72) and for CD4 351 to 500 when compared with CD4 201 to 350 cells/mm 3 (aHR 0.84, 95% CI 0.72 to 1.00). ART initiation varied over time for TB cases, with lower hazard during the first two weeks after HIV care enrolment and higher hazards thereafter. Of patients with advanced HIV disease (n = 1085; 36.0%), crude 3‐month ART initiation was similar in both interventions (91% to 92%) although Treat‐All initiated patients more quickly during the first month after HIV care enrolment. Conclusions: ART initiation was high under Treat‐All and without evidence of de‐prioritization of patients with advanced HIV disease. Additional studies are needed to understand the long‐term impact of Treat‐All on patient outcomes.